Planned private homebirth in Victoria 2000-2015: a retrospective cohort study of Victorian perinatal data - Miranda L. Davies-Tuck; Euan M. Wallace; Mary-Ann Davey; Vickie Veitch; Jeremy Oats (BMC, 2018)
Abstract Background The outcomes for planned homebirth in Victoria are unknown. We aimed to compare the rates of outcomes for high risk and low risk women who planned to birth at home compared to those who planned to birth in hospital. Methods We undertook a population based cohort study of all births in Victoria, Australia 2000-2015. Women were defined as being of low or high risk of adverse pregnancy outcomes according to the eligibility criteria for homebirth and either planning to birth at home or in a hospital setting at the at the onset of labour. Rates of perinatal and maternal mortality and morbidity as well as obstetric interventions were compared. Results Three thousand nine hundred forty-five women planned to give birth at home with a privately practising midwife and 829,286 women planned to give birth in a hospital setting. Regardless of risk status, planned homebirth was associated with significantly lower rates of all obstetric interventions and higher rates of spontaneous vaginal birth (p ≤ 0.0001 for all). For low risk women the rates of perinatal mortality were similar (1.6 per 1000 v's 1.7 per 1000; p = 0.90) and overall composite perinatal (3.6% v's 13.4%; p ≤ 0.001) and maternal morbidities (10.7% v's 17.3%; p ≤ 0.001) were significantly lower for those planning a homebirth. Planned homebirth among high risk women was associated with significantly higher rates of perinatal mortality (9.3 per 1000 v's 3.5 per 1000; p = 0.009) but an overall significant decrease in composite perinatal (7.8% v's 16.9%; p ≤ 0.001) and maternal morbidities (16.7% v's 24.6%; p ≤ 0.001). Conclusion Regardless of risk status, planned homebirth was associated with significantly lower rates of obstetric interventions and combined overall maternal and perinatal morbidities. For low risk women, planned homebirth was also associated with similar risks of perinatal mortality, however for women with recognized risk factors, planned homebirth was associated with significantly higher rates of perinatal mortality.